Syah Waliullah al-Dihlawi (1703-1762) : Tokoh Kebangkitan Islam Abad 18 - Sofia, Desmi; Fatimah, Siti (Jurnal Kronologi, 2024)
Islam experienced development in India from the 13th century to the mid-19th century. Meanwhile, the period of revival and the emergence of reform ideas in Islamic thought appeared in the 18th century. This study aims to examine one of the figures of Islamic revival and reform in India, Shah Waliullah al-Dihlawi (1703-1762), who contributed to social and economic knowledge in Islam following the collapse of the Mughal dynasty. This research is a historical study that uses steps such as data collection (heuristics), source criticism (verification), interpretation, and historical writing, or historiography. The results of this study show that Shah Waliullah al-Dihlawi made contributions in the fields of Tafsir, Hadith, Sufism, and other disciplines. In the field of economics, Shah Waliullah al-Dihlawi emphasized fair and interest-free economics, in accordance with Islamic law.